Trypsin causes platelet activation independently of known protease-activated receptors - Mao, Yingying; Kunapuli, Satya P. (Thrombosis and Haemostasis, 2013)
To identify a physiological agonist of PAR3, we used PAR4 null murine platelets, which were known to express only PAR3. In this study, we tested several proteases and found that trypsin, but not heat-inactivated trypsin, activated PAR4 null murine platelets. Even at high concentrations, trypsin caused shape change without increasing intracellular calcium levels in PAR4 null murine platelets. Consistent with this result, the Gq inhibitor YM-254890 had no effect on trypsin-induced shape change. However, trypsin-induced platelet shape change was abolished by either p160ROCK inhibitor, Y27632 or H1152. Furthermore, trypsin caused phosphorylation of myosin light chain (Thr18), but not Akt or Erk. Surprisingly, trypsin caused a similar shape change in PAR4-desensitised PAR3 null murine platelets as in PAR4 null murine platelets, indicating that trypsin did not activate PAR3 to cause shape change. More interestingly, the Src family kinase (SFK) inhibitor PP2 abolished trypsin-induced, but not AYPGKF-induced, shape change. Hence, trypsin activated a novel signalling pathway through RhoA/p160ROCK and was regulated by SFKs. In conclusion, our study demonstrates a novel protease signalling pathway in platelets that is independent of PARs. This protease-induced novel signalling pathway regulates platelet shape change through SFKs and p160ROCK.
Keywords: Trypsin; protease-activated receptor; platelet shape change